Development of Interactive Learning Multimedia for Biology Subjects on the Human Blood Circulation System Material to Improve Motivation and Learning Outcomes in High School - Perkasa Gadik Puriadi; Herman Dwi Surnjono (Jurnal Penelitian Pendidikan IPA, 2024)
Lack of student learning motivation will cause low learning outcomes. One of the students' needs for learning understanding is through appropriate learning media. The development of learning media has a role in improving students' understanding and learning motivation. This study aims to determine the level of feasibility and effectiveness of learning multimedia developed as a biology learning media for the material Human Blood Circulation System for grade XI students. The development model used in this study is ADDIE. Multimedia product testing is carried out in two stages, namely the alpha-beta test used to determine the feasibility of the product and the product effectiveness test to determine the effectiveness of the product in improving learning outcomes and student motivation. The alpha test was carried out by involving two experts in the fields of media and materials. The beta test stage was carried out by involving 1 biology teacher and 5 grade XI students of SMAN 1 Sleman. The effectiveness test stage was carried out by involving 30 students. Data collection techniques were carried out by means of observation, interviews, questionnaires and tests. Data analysis in this study used qualitative descriptive analysis. The results of the product testing obtained an alpha test on media experts with an average value of 3.64 and on material experts with an average value of 3.38 which is included in the very eligible category. The results of the beta test obtained an average value of 3.49 which is also included in the very eligible category. The results of the effectiveness test also showed positive results, namely learning outcomes that increased from an average of 52.2 to 95.8. The learning motivation aspect also showed an increase from the moderate category to high.